PENERAPAN MEDIA VIDEO TUTORIAL RIAS WAJAH FILM DRAMA KOREA TRUE BEAUTY DI SMK NEGERI 1 POGALAN - Citra Panca Paramita; Octaverina Kecvara Pritasari; Dewi Lutfiati; Sri Dwiyanti (Jurnal Tata Rias, 2025)
Video tutorials are one form of learning media that can provide a more interesting learning experience and help improve student understanding. This study aims to evaluate the feasibility of learning media, measure student learning outcomes, and identify student responses to the use of the media. The type of research used is R&D (Research and Development) the development model used is 4D (Define, Design, Develop, Dissemination). The data collection methods used are observation, psychomotor learning outcome tests, and questionnaires. The data collection instruments used are media feasibility observation sheets, learning outcome test questions, and student response questionnaire sheets. The objects and subjects of this study were film make-up and 36 class XI TKKR 2 SMKN 1 Pogalan students. Data were analyzed using the calculation of average values. The results of the study showed that: (1) Assessment of media feasibility from the aspects of media, materials, and language produced an average score of 4.77 which is included in the "very feasible" category; (2) Students' psychomotor scores reached an average of 86, which exceeded the KKTP of 80, so that it was declared complete overall; (3) Student responses to learning media showed an average score of 4.84 with the category "very appropriate". From these findings, it can be concluded that video tutorial media is very effective for use in the learning process. Keywords: Media Development, Video Tutorials, Film Makeup, Korean Drama True Beauty.